Private and Public Initiatives : Working Together for Health and Education - Gaag, Jacques van der.; World Bank, Washington, DC. (Washington : ERIC Clearinghouse, 1995)
The World Bank helps countries to arrive at whatever combination of public and private control is best for their particular economic circumstances. This booklet describes that work and summarizes examples of private-sector involvement in health and education provision in the developing world today. The examples also illustrate what the World Bank is doing to help bring those outside government-communities, nongovernmental organizations (NGOs), private voluntary organizations, private providers, and corporations--into the design and implementation of social-service projects. Part 1 describes the historical roots of present trends--the development of modern health care systems, mass education systems--and the inequities that currently exist in health and education. The role of the World Bank in eliminating the social deficit and reducing poverty worldwide is described. The World Bank advocates using competitive markets to organize the production and distribution of goods and services and using a market-oriented approach to development. Part 2 offers examples of World Bank assistance in Kenya, Pakistan, Bolivia, India, Columbia, Burkina Faso, Mexico, Panama, Peru, Uruguay, Estonia, and Brazil. Sixteen boxes, 5 figures, and 2 tables are included. (Contains 63 references.) (LMI)
Availability: The World Bank, 1818 H Street, N.W., Washington, DC 20433.
Microfiche.
Keywords: Access to Education